Prognostic value of FLOT1-related gene signature in head and neck squamous cell carcinoma: insights into radioresistance mechanisms and clinical outcomes - Min Kyeong Lee; Seon Rang Woo; Joo Kyung Noh; MinJi Bae; YeonSeo Lee; Soonki Min; Moonkyoo Kong; Young Chan Lee; Seong‐Gyu Ko; Young-Gyu Eun (Cell Death Discovery)
Abstract We aimed to develop and validate the ability of a FLOT1-related gene signature to predict survival in head and neck squamous cell carcinoma (HNSCC) patients and to explore FLOT1’s role in modulating the responses to radiation therapy (RT). Using TCGA dataset, we identified a gene expression signature reflective of FLOT1 and applied LASSO regression to build a prediction model. Patients were stratified into high- and low-risk subgroups based on this signature. The prognostic value was confirmed across three independent cohorts, showing that high-risk patients had significantly poorer overall survival. Cox proportional hazards models were used to establish this gene signature as an independent prognostic factor for overall survival in HNSCC patients. Additionally, this signature predicted survival outcomes in patients undergoing RT. In vitro and in vivo experiments revealed that inhibiting FLOT1 expression increased the radiation sensitivity of HNSCC cells by modulating the phospho-PTEN/IGF1R axis. Moreover, silencing FLOT1 decreased radioresistance in radioresistant cell lines and xenograft mouse models. In conclusion, the FLOT1-related gene signature is a strong prognostic marker for HNSCC and may help identify patients who may benefit from RT.